Genotoxicity and cytotoxicity of three microcystin-LR containing cyanobacterial samples from Antioquia, Colombia (2018)
ABSTRACT: The presence of cyanobacterial blooms and cyanotoxins in water presents a global problem due to the deterioration of ecosystems and the possibility of poisoning in human and animals. Microcystin LR is the most widely distributed cyanotoxin and liver cells are its main target. In the present study, HepG2 cells were used to determine DNA damage of three crude extracts of cyanobacterial blooms containing MC-LR, through comet assay. The results show that all extracts at a concentration of 500 μg mL−1 caused low damage in hepatocytes exposed for 24 h, but produced total mortality even at low concentrations at 48 h. Moreover, balloons corresponding to cell apoptosis were found. Through HPLC/MS, MC-LR was detected in all samples of cyanobacterial blooms at concentrations of (5,65 μg ml−1) in sample 1, (1,24 μg ml−1) in sample 2 and (57,29 μg ml−1) in sample 3. In addition, in all samples high molecular weights peaks were detected, that may correspond to other microcystins. Besides, the cytotoxic effect of a cyanobacterial bloom and some of its chromatographic fractions from the crude extracts were evaluated in U-937, J774, Hela and Vero cell lines, using the enzymatic micromethod (MTT). The highest toxicity was detected in U-937 cells (LC50 = 29.7 μg mL−1) and Vero cells (LC50 = 39.7 μg mL-1). Based on these results, it is important to remark that genotoxic and cytotoxicity assays are valuable methods to predict potential biological risks in waters contaminated with blooms of cyanobacteria, since chemical analysis can only describe the presence of cyanotoxins, but not their biological effects.